One Belt, One Road, One Story?
XI, 282 p. 2 illus.
Keywords: This book explores the emerging EU-China relationship with a focus on the impact of the Belt and Road Initiative. It takes a narrative approach to understanding the EU-China relationship as a means to highlight how scholars in the EU and China interpret the narrativization of EU-China bilateral relations and to how this bilateral relationship is refracted through relations with third parties. The volume brings together scholars from China and Europe in the fields of Chinese foreign policy, EU studies, and strategic communication. The empirical focus cuts across policy, publics and media, and across history, political economy and diplomacy. The Belt and Road Initiative, alongside the other policy areas addressed in the chapters, offers ways for people in Europe and China to get to know one another in new ways, and for the EU and its member states and the Chinese state to forge new partnerships.